2015
DOI: 10.1074/jbc.m114.618785
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Curcumin Degradation

Abstract: Background:The bioactive metabolites of curcumin are not well defined. Results: Using [14 C]curcumin as tracer, degradation products and unstable reaction intermediates were isolated and identified. Conclusion: The spontaneous degradation of curcumin is an autoxidation that yields electrophilic and nucleophilic products. Significance: The unexpected chemical diversity of its metabolites may explain the polypharmacology of curcumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 57 publications
6
89
1
Order By: Relevance
“…52 For example, a recently identified degradation product of 1 is a spiroepoxide, which is highly sensitive to acids and reacts readily with thiols. 53 This report indirectly emphasizes the relevance of dynamic RC by hypothesizing that the polypharmacology of 1 may in part, or even largely, be due to the sum of its degradation products.…”
Section: Curcumin Is a Pains Imps And Poor Lead Compoundmentioning
confidence: 93%
“…52 For example, a recently identified degradation product of 1 is a spiroepoxide, which is highly sensitive to acids and reacts readily with thiols. 53 This report indirectly emphasizes the relevance of dynamic RC by hypothesizing that the polypharmacology of 1 may in part, or even largely, be due to the sum of its degradation products.…”
Section: Curcumin Is a Pains Imps And Poor Lead Compoundmentioning
confidence: 93%
“…82 The polyphenolic compound, curcumin is only slightly soluble in an aqueous environment, experiences degradation at alkaline pH, rapidly metabolized and conjugated in the liver (curcumin sulfate and curcumin glucuronide), undergoes rapid systemic elimination, is excreted in feces, demonstrates poor tissue absorption, and characterized as a Class II drug 8385 . In vitro application as a pharmaceutical agent is challenged by curcumin’s degradation and in vivo administration results in decreased efficacy because of metabolic changes.…”
Section: Introductionmentioning
confidence: 99%
“…2B). Formation of a spiroepoxide suggested that the reaction proceeded analogous to the oxidative transformation of curcumin (21). When curcumin-glucuronide was transformed using the oxidizing agent potassium ferricyanide (K 3 Fe(CN) 6 ) a similar decrease at 430 nm and increase at ≈260 nm were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The major pathway of non-enzymatic degradation of curcumin at physiological pH is an oxidative transformation leading to dioxygenated bicyclopentadione (BCP) diastereomers (Fig. 1B) (21). Oxidative transformation of curcumin occurs spontaneously as autoxidation and can also be catalyzed by the peroxidase activity of cyclooxygenase-2 (10).…”
Section: Introductionmentioning
confidence: 99%